The Relationship between of Rural Accessibility and Development - Thomas Soseco (Universitas Negeri Malang, 2016)
Rural accessibility has been an important issue for development. As wider accessibility allow people to increase their living standard, there is an urgency to compose a single indicator to measure accessibility. The World Bank has been produced Rural Access Index (RAI). That index measure the percentage of rural population living within two kilometers from all-season road. Even though this index is useful to compare among countries, there are obstacles experienced especially in developing countries like Indonesia. The first barrier is data availability. Then, the second barrier is the unequal population distribution in Indonesia. However, the index is still needed to solve many problems in Indonesia, e.g. health and lack of infrastructure.Keywords: Rural Access Index (RAI), accessibility, rural areaJEL Classification: O18, R11, R12